Efficacy of dental floss and chlorhexidine mouth rinse as an adjunct to toothbrushing in removing plaque and gingival inflammation - a three way cross over trial - Arora, Vikram; Tangade, Pradeep; T L, Ravishankar; Tirth, Amit; Pal, Sumit; Tandon, Vaibhav (Journal of clinical and diagnostic research, 2014)
Maintaining good oral hygiene is important to combat periodontal diseases. The use of tooth brush alone does not serve the purpose of removing plaque which demands the use of some adjuncts such as proximal cleaning aids. The study was conducted to compare the efficacy of Dental Floss and 0.12% Chlorhexidine Gluconate Mouthrinse as an adjunct to toothbrushing on plaque accumulation and gingival inflammation. Department of Public Health Dentistry, Kothiwal Dental College and Research Centre, Moradabad, India. This was a randomized, double blind, three-way cross over clinical trial. Forty five dental students in the age group of 19-25yr. were enrolled into the study. Subjects were randomly assigned into three groups (n=15) i.e. Group A- Toothbrushing with Dental floss (TB+DF), Group B- Toothbrushing with 0.12% Chlorhexidine Gluconate Mouthrinse (TB+CHX-MR) and Group C- Toothbrushing alone (TB Alone) in a three-way crossover manner. After 21 d of trial period, plaque index (PI) and gingival index (GI) were assessed for each group, oral prophylaxis followed by a washout period for 14d. Mean, standard deviations and p-values were obtained. ANOVA test was used to compare the intergroup difference and Post hoc test to compare between the two groups. The inter-group comparison for GI and PI at all interventions showed statistically significant difference (p<0.001). While comparing between group A and group C at second and third follow up, no significant difference were observed though group A showed reduction in mean values for both the clinical parameters whereas while comparing between group A and group B, statistically significant difference was observed, which is in line when compared with group B and group C. The Group B showed more reduction in plaque and gingival scores which was found to be statistically significant (p<0.001). CHX-MR when used as an adjunct to toothbrushing is more effective in the reduction of plaque and gingival scores than a toothbrush alone or in combination with DF.